We'll re-write the
equation:
`(x+i)^n + (x-i)^n =
0`
We'll divide by `(x-i)^n` both
sides:
`((x+i)/(x-i))^n + 1 =
0`
We'll subtract 1 both
sides:
`((x+i)/(x-i))^n = -1` We'll write -1 as a
trigonometric form of a complex number:
`-1 = cos pi + isin
pi`
We'll re-write the
equation:
`((x+i)/(x-i))^n = cos pi + isin
pi`
We'll remove the n-th power from the left side, raising
both sides to the power `(1/n):`
`` `(x+i)/(x-i) = (cos pi
+ isin pi)^(1/n)`
We'll apply Moivre's rule to the right
side:
`(x+i)/(x-i) = (cos ((2k+1)pi/n) + isin
((2k+1)pi/n))` k is an integer number.
We'll multiply the
denominator from the left side, by it's
conjugate:
`(x+i)^2/((x+i)(x-i)) = (cos ((2k+1)pi/n) + isin
((2k+1)pi/n))`
The difference of squares from denominator
returns the product `x^2 + 1` .
We'll cross multiply and
we'll get:
`x^2 + 2ix - 1 = (x^2 + 1)(cos ((2k+1)pi/n) +
isin ((2k+1)pi/n))`
`x^2 + 2ix - 1 = (x^2 + cos
((2k+1)pi/n)) + i(x^2*sin ((2k+1)pi/n) + sin
((2k+1)pi/n))`
We'll compare both
sides:
`x^2 - 1 = x^2 + cos
((2k+1)pi/n)`
`` `cos ((2k+1)pi/n) =
-1`
`` `2x = x^2*sin ((2k+1)pi/n) + sin
((2k+1)pi/n)`
`sin[((2k+1)pi/n]= (2x)/(x^2 +
1)`
`x_k = cot
[((2k+1)pi)/(2n)]`
Therefore, the solutions
of the given equation are: `x_k = cot [((2k+1)pi)/(2n)].`
No comments:
Post a Comment